2021
DOI: 10.1016/j.asmr.2021.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Overprescribing and Undereducating: a Survey of Pre- and Postoperative Pain Protocols for Pediatric Anterior Cruciate Ligament Surgery

Abstract: Purpose: To establish a better understanding of the variations in pain management protocols and prescribing patterns for pediatric patients undergoing anterior cruciate ligament (ACL) reconstruction or repair. Methods: A 20-question multiple-choice survey was distributed to 3 professional orthopaedic societies to assess the pre-emptive and postoperative pain management prescribing patterns for pediatric patients undergoing ACL reconstruction or repair. Clinical agreement (defined as agreement between >80% of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…The main reason for not instructing patients was being uninformed about the proper ways of disposing of opioid pain medication. This finding is in line with a recent survey that was published by Perry et al 30 that reported 63% of physicians did not counsel patients on how to dispose of unconsumed opioid tablets. This demonstrates a gap in providing education about safe prescribing practices.…”
Section: Postoperative Pain Managementsupporting
confidence: 91%
“…The main reason for not instructing patients was being uninformed about the proper ways of disposing of opioid pain medication. This finding is in line with a recent survey that was published by Perry et al 30 that reported 63% of physicians did not counsel patients on how to dispose of unconsumed opioid tablets. This demonstrates a gap in providing education about safe prescribing practices.…”
Section: Postoperative Pain Managementsupporting
confidence: 91%
“…One study surveying the prescribing practices of opioids to pediatric patients after ACLR demonstrated that 48% of surgeons prescribed 11 to 19 opioid tablets and 25% prescribed 6 to 10 tablets. 12 Pain medication prescribing practices have also been demonstrated as undertreating pain in Black and Hispanic patients with White patients being more likely to receive opioid prescriptions than other racial and ethnic groups. 13,14 Beck et al 15 found the median number of hydrocodone/acetaminophen 5/325 mg consumed by their adolescent patients after ALCR with or without meniscal treatment was less than half of what was prescribed (17/40 tablets).…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively, these current results maintain 72% of patients did not require postoperative opioids in the SPNB+B group, and 93% of patients did not consume narcotics in the SPNB+BL group. One study surveying the prescribing practices of opioids to pediatric patients after ACLR demonstrated that 48% of surgeons prescribed 11 to 19 opioid tablets and 25% prescribed 6 to 10 tablets 12 . Pain medication prescribing practices have also been demonstrated as undertreating pain in Black and Hispanic patients with White patients being more likely to receive opioid prescriptions than other racial and ethnic groups 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“… 1 Studies have also shown that up to 88% of orthopaedic surgeons prescribe opioids after ACLR to the pediatric population. 12 It is interesting to note that many studies have reinforced the notion that these high quantities of opioids provide no added benefit for pain outcomes after ACLR. A study by Hartwell et al.…”
Section: Discussionmentioning
confidence: 99%